Urinary extracellular vesicles contain mature transcriptome enriched in circular and long noncoding RNAs with functional significance in prostate cancer. Issue 5 (8th May 2022) - Almeida, Anna; Gabriel, Marc; Firlej, Virginie; Martin‐Jaular, Lorena; Lejars, Matthieu; Cipolla, Rocco; Petit, Floriane; Vogt, Nicolas; San‐Roman, Mabel; Dingli, Florent; Loew, Damarys; Destouches, Damien; et al.
Abstract: Long noncoding (lnc)RNAs modulate gene expression alongside presenting unexpected source of neoantigens. Despite their immense interest, their ability to be transferred and control adjacent cells is unknown. Extracellular Vesicles (EVs) offer a protective environment for nucleic acids, with pro and antitumourigenic functions by controlling the immune response. In contrast to extracellular nonvesicular RNA, few studies have addressed the full RNA content within human fluids' EVs and have compared them with their tissue of origin. Here, we performed Total RNA‐Sequencing on six Formalin‐Fixed‐Paraffin‐Embedded (FFPE) prostate cancer (PCa) tumour tissues and their paired urinary (u)EVs to provide the first whole transcriptome comparison from the same patients. UEVs contain simplified transcriptome with intron‐free cytoplasmic transcripts and enriched lnc/circular (circ)RNAs, strikingly common to an independent 20 patients' urinary cohort. Our full cellular and EVs transcriptome comparison within three PCa cell lines identified a set of overlapping 14 uEV‐circRNAs characterized as essential for prostate cell proliferation in vitro and 28 uEV‐lncRNAs belonging to the cancer‐related lncRNA census (CLC2). In addition, we found 15 uEV‐lncRNAs, predicted to encode 768 high‐affinity neoantigens, and for which three of the encoded‐ORF produced detectable unmodified peptides by mass spectrometry. Our dual analysis of EVs‐lnc/circRNAs both in urines' and in vitro's EVs provides a fundamental resource for future uEV‐lnc/circRNAs phenotypic characterization involved in PCa.